Evaluation of ground corn germ as an energy source in nursery diets - Hastad, C.W.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundred eighty nursery pigs (initially 30.9 lb) were used in a 21-d growth assay to determine the energy value of ground corn germ relative to corn oil in nursery diets. Increasing dietary corn oil linearly decreased average daily feed intake and improved feed efficiency. However, pigs fed diets containing ground corn germ meal had similar gain and feed efficiency as those fed the corn-soybean meal diet without added fat. These results suggest that the added energy provided by corn germ is not utilized as well as that from corn oil.
Keywords: Swine; Nursery pigs; Corn germ; Energy source; Fat